FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MASYARAKAT MEMBELI RUMAH BERSUBSIDI DI KECAMATAN MEDAN MARELAN - Manda Dwipayani Bhastary (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2016)
Along with the increasingly difficult economic situation and the many demands need to be met  by the community then purchase a house in cash more difficult, especially for people who are middle to lower economic level. Thus, the purchase of subsidized home loans  among  people  becomes  a  very  attractive  option.  Based  on  data  collected  by  an increase  in  the  demand  for  subsidized  housing,  especially  in  the  district  of  Medan Marelan. It can be seen from the increasing property business. Private developers tend to be  more  interested  in  the  property  business  (houses)  in  the  district  of  Medan  Marelan because the area is still beautiful and population growth rates are higher. The high level of competition among developers of property (housing), makes an analysis of the factors that influence  the  decision  of  the  community  in  need  of  subsidized  housing  memebeli  known.This study aimed to analyze and determine whether the factor of location, public revenues, ease  of  access  to  credit,  and  public  facilities,  the  market  price  of  the  home  as  well  as legislation affecting people's decision in the purchase of subsidized  housing in the district of Medan Marelan.The  results  showed  that  the  location  factor  is  the  most  dominant  factor  of  the factors that influence the decision to buy subsidized housing communities in the district of Medan Marelan with a coefficient of determination of 42.1%.Keywords: Purchase Decision Factors